2008
DOI: 10.1248/bpb.31.2114
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory Activity of Prosapogenin Methyl Ester of Platycodin D via Nuclear Factor-kappaB Pathway Inhibition

Abstract: Immune responses to infection or to localized injury or trauma are among the main causes of local or systemic inflammation. Despite the beneficial effect of inflammation in limiting responses to cellular and organ damage, a breakdown in the regulation of the inflammatory response may result in a wide range of chronic diseases such as arthritis, inflammatory bowel diseases, asthma and others. 1)Non-steroidal anti-inflammatory drugs (NSAIDs), such as aspirin, sulindac and indomethacin, are widely believed to hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
40
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 47 publications
4
40
0
2
Order By: Relevance
“…Platycodin D (PD, Fig. 1), the major active constituent of P. grandiflorum, has received more and more attention due to its pharmaceutical effects, including anti-inflammation (Chung et al, 2008;Zhang et al, 2015), anti-obesity (Zhao et al, 2006), anti-atherosclerosis (Wu et al, 2012), hepatoprotective Li et al, 2015a), and anti-tumor (Luan et al, 2014;Zhao et al, 2015) effects. It is worth mentioning that PD exerts remarkable anti-cancer effects on different kinds of cancer cell lines, including HepG2, MDA-MB-231, U937, K562, PC3, and MCF-7, with main molecular mechanisms such as promoting apoptosis and inhibiting migration and invasion (Tang et al, 2014;Li et al, 2014;Yu and Kim, 2010;Shin et al, 2009;Kim et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Platycodin D (PD, Fig. 1), the major active constituent of P. grandiflorum, has received more and more attention due to its pharmaceutical effects, including anti-inflammation (Chung et al, 2008;Zhang et al, 2015), anti-obesity (Zhao et al, 2006), anti-atherosclerosis (Wu et al, 2012), hepatoprotective Li et al, 2015a), and anti-tumor (Luan et al, 2014;Zhao et al, 2015) effects. It is worth mentioning that PD exerts remarkable anti-cancer effects on different kinds of cancer cell lines, including HepG2, MDA-MB-231, U937, K562, PC3, and MCF-7, with main molecular mechanisms such as promoting apoptosis and inhibiting migration and invasion (Tang et al, 2014;Li et al, 2014;Yu and Kim, 2010;Shin et al, 2009;Kim et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Platycodin D (PD), a triterpenoid saponin derived from the roots of Platycodin grandiflorum, has been reported to possess a wide rangeof health benefits, such as anti-atherosclerotic (4), anti-inflammatory (5,6), hypocholesterolemic, and anti-obesity effects (7), as well as spermicidal and contraceptive activity (8). Among the various health benefits of PD, anticancer effects have been noted in several cancer cell lines, including lung cancer cells (9), hepatocellular carcinoma cells (10), gastric cancer cells (11), prostate cancer cells (12), and leukemia cells (13,14).…”
Section: Introductionmentioning
confidence: 99%
“…Platycodin D is a bioactive triterpenoid saponin that is isolated from the root of Platycodon grandiflorum (Companulaceae) and possesses various pharmacological activities, including anti-cancer, anti-angiogenic, anti-inflammatory, and anti-obesity effects [10,11,12,13,14]. In particular, many studies have reported the anti-cancer effects of platycodin D in breast cancer cells.…”
Section: Introductionmentioning
confidence: 99%